LπCET: A Logic Security Analysis for Cryptographic Protocols Based on π-Calculus Extension Theory - Fusheng Wu; Jinhui Liu; Yanbin Li; Mingtao Ni (IET Information Security)
The π-calculus is a basic theory of mobile communication based on the notion of interaction, which, is aimed at analyzing and modeling the behaviors of communication processes in communicating and mobile systems, and is widely applied to the security analysis of cryptographic protocol’s design and implementation. But the π-calculus does not provide seamless logical security analysis, so the logical flaws in the design and the implementation of a cryptographic protocol cannot be discovered in time. This paper introduces logical rules and logical proofs, binary tree, and the KMP algorithm and proposes a new extension of the π-calculus theory, a logical security analysis method, and an algorithm. The aim is to analyze whether there are logical flaws in the design and the implementation of a cryptographic protocol, to ensure the security of the cryptographic protocol when it is encoded into software and implemented. This paper presents the logical security proof and analysis of the TLS1.3 protocol’s interactional implementation process. Empirical results show that the additional extension theory, the logical security analysis method, and the algorithm can effectively analyze whether there are logical flaws in the design and the implementation of a cryptographic protocol.